PENERAPAN SISTEM INFORMASI ADMINISTRASI BARANG PADA TOKO KASIH DUATO - Genrawan Hoendarto; Kartono Kartono; Antonius Maspro (INTEKSIS, 2023)
Information Systems Purchase and Sale of Goods is a system that provides information services in the form of data sales and purchase of goods and goods. The existence of this information system is important. In this case, Toko Kasih Duato serve as a place of research, because the system of sales information and purchases of goods in place has not been well managed so often there is a mistake in making existing reports, such as data processing transaction sales, data processing purchase transaction, data processing goods, and member supplier data processing. The purpose of this study is to provide convenience at the time of data processing of goods, customers and suppliers, facilitate the processing of sales and purchase transaction data, minimize errors in the recording of data purchases and sales data per period. The purpose of the research produced several uses consisting of practical and academic uses. Writing used by the author for this thesis is descriptive research design that tries to describe the object or subject in carefully as it is, While the method of data collection the author using Obsevation method, interview and Document Research, for system analysis techniques used by the authors in research on Toko Kasih Duato this is, Unified Modeling Language (UML), System design techniques used programming language used to build the system and its manufacture is a programming language Microsoft Visual Basic 6.0, Microsoft Office Access 2007 for designing databases, and reports printed using Crystal Report 8.5. Keywords: Sales and purchase information system, Microsoft Office Access 2007. Crystal Report 8.5.